99 PEMBUATAN BAHAN FILTER KERAMIK BERPORI BERBASIS ZEOLIT ALAM DAN ARANG SEKAM PADI - Sebayang, P.; Muljadi, -; Tetuko, Anggito P. (LIPI Press, 2009)
The porous ceramics filter material have been made from natural zeolit and rice husk charcoal with composition variation (in % of mass). The preparation of zeolit was done using ball mill for 24 hours and rice husk charcoal was prepared using vibrating mill for 1 hour until it can be through out in 100 mesh shieve. The two raw materials about 2 grams were mixed with addition 50 ml of Polivinylalcohol (PVA), then it was mixed again until homogeny. The sample was dried pressed with pressure of 25 kgf/cm and dried in a drying oven at 60 C for 24 hours. The sintering process was done using electrical furnace with heating rate of 10C/minute until it reached temperature of 900 and 1000 C, and holded for 2 hours. From the result of porouc ceramics filter material, the optimum composition is 40% rice husk coke + 60% Zeolit with sintering temperature = 1000 C. At this condition, the properties are density = 2,16 g/cm, shrinkage = 35,94%, porosity = 66,05%, water absorption = 31,10%, modulus of rupture = 7,47 MPa, compressive strength = 4,38 MPa, and coefficient of thermal expansion = 5 x 10 -6 C-1. The result of XRD shows that zeolit has major phase of mordenite (Na8[Al8Si40O96].24H2O) and minor phase of clinoptilolite (Na6[Al6Si36O72].24H2O). The result of XRD on 40% rice husk coke + 60% Zeolit and sintering temperature = 1000 C shows that the major phase is mullite (3Al2O3SiO2) and the minor phase is tridimite (SiO2). Meanwhile, the picture of SEM shows that porous ceramics have irregular particle with size between 110 ?m and its pore size can reaches 20 ?m.